Construction of the graph of reducing uncertainty in implementing of investment projects portfolio - Ванюшкин, Александр Сергеевич (Eastern-European Journal of Enterprise Technologies, 2012)
The test of the general theoretical graph of reducing uncertainty on the project is done, the expediency of the use of graphics to reduce uncertainty for the identification of the project is grounded, which should be given maximum attention, as well as to determine when the time switch attention to other projects within the portfolio